2019
DOI: 10.1103/physrevb.100.104112
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of electronic stopping power in graphite

Abstract: The rate of energy transfer from ion projectiles onto the electrons of a solid target is hard to determine experimentally in the velocity regime between the adiabatic limit and the Bragg peak. First-principles simulations have lately offered relevant new insights and quantitative information for prototypical homogeneous materials. Here we study the influence of structural anisotropy on electronic stopping power with time-dependent density functional theory simulations of a hydrogen projectile in graphite. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…95 The difference of sign between protons and antiprotons produces a significant difference in the stopping power (rate of energy excitation) beyond the linear-response paradigm (the Barkas effect), and the insulating character of the target makes it inaccessible to the jellium paradigm. The success stimulated further studies along this line [77][78][79][80] using improved versions of TD-DFT in SIESTA, as described here. Fig.…”
Section: Electronic Stopping Of Atomic Projectilesmentioning
confidence: 93%
See 2 more Smart Citations
“…95 The difference of sign between protons and antiprotons produces a significant difference in the stopping power (rate of energy excitation) beyond the linear-response paradigm (the Barkas effect), and the insulating character of the target makes it inaccessible to the jellium paradigm. The success stimulated further studies along this line [77][78][79][80] using improved versions of TD-DFT in SIESTA, as described here. Fig.…”
Section: Electronic Stopping Of Atomic Projectilesmentioning
confidence: 93%
“…75, this algorithm can be shown not to be entirely consistent with the connection represented by the D matrix defined above. Nevertheless, the discrepancies due to the mentioned inconsistency have been shown to be small in a series of studies using this formalism [77][78][79][80] , at least for low atomic velocities. The practical benefit of separating the two procedures is to perform the change of basis only when necessary, allowing for many electronic steps per atomic motion step, if the nuclei are still significantly slower than electrons, for instance.…”
Section: H Time Dependent Dftmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have highlighted the different contributions of semicore electrons in channelling versus off-channelling conditions [ 35 ]. Local enhancement and reduction of the ESP for specific channels and velocity-dependent deviations from an ideal channelling trajectory were also reported [ 31 ], as well as the influence of a strongly anisotropic crystal structure on the stopping power [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Computational modeling of electron dynamics during ion irradiation of materials offers opportunities to accurately predict optimal beam and detector parameters for nondestructive imaging of 2D materials. Many studies have demonstrated the ability of first-principles calculations to predict accurate energy deposition rates for ions traversing bulk materials [23][24][25][26][27][28][29]. However, projec-tile charge may not fully equilibrate within a thin target [30][31][32], fundamentally altering the response of these materials to ion irradiation.…”
Section: Introductionmentioning
confidence: 99%